2022
DOI: 10.3389/fpls.2022.810905
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide, a Novel Nanomaterial as Soil Water Retention Agent, Dramatically Enhances Drought Stress Tolerance in Soybean Plants

Abstract: Drought is one of the most severe environmental stressors that place major constraints on the growth of soybeans (Glycine max L.). Graphene oxide (GO) is a nanomaterial that can promote plant growth without toxic effects. In this study, the physiological and molecular responses to drought stress with GO treatment were examined. We discovered that the relative water content (RWC) of stems and leaves treated with GO was 127 and 128% higher than that of the WT plants, respectively. The root parameters in GO-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Increased nutrient availability to lettuce plants, derived by GO and its physicochemical properties as reported ( Lahiani et al., 2015 ; Kabiri et al., 2017 ; Juarez-Maldonado et al., 2019 ; Carneiro et al., 2022 ), could have been one of the possible reasons. Another mechanism of beneficial interaction of GO and elemental sulfur could have been a positive effect on soil water retention as referred to by ( Zhao et al., 2020 ; Zhao et al., 2022 ). In the previously published study by ( Hammerschmiedt et al., 2022 ), in which the lettuce plants were illuminated by color (blue+red) light instead of artificial white light, the plant biomass yield responded to GO and co-applied S 0 + GO differently, showing the significantly higher AGB values than other amended soil variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased nutrient availability to lettuce plants, derived by GO and its physicochemical properties as reported ( Lahiani et al., 2015 ; Kabiri et al., 2017 ; Juarez-Maldonado et al., 2019 ; Carneiro et al., 2022 ), could have been one of the possible reasons. Another mechanism of beneficial interaction of GO and elemental sulfur could have been a positive effect on soil water retention as referred to by ( Zhao et al., 2020 ; Zhao et al., 2022 ). In the previously published study by ( Hammerschmiedt et al., 2022 ), in which the lettuce plants were illuminated by color (blue+red) light instead of artificial white light, the plant biomass yield responded to GO and co-applied S 0 + GO differently, showing the significantly higher AGB values than other amended soil variants.…”
Section: Discussionmentioning
confidence: 99%
“…GO is quite mobile in soil ( Sangani et al., 2019 ; Xia et al., 2021 ); however, its leaching can be reduced by aggregation mediated by Ca 2+ in concentration ≥ 0.5 mM ( Qi et al., 2014 ). Amendment of GO to soil alters its hygroscopic and adsorptive capabilities and water content, and reduces the impact of drought stress ( Zhao et al., 2020 ; Zhao et al., 2022 ); as a carrier, it increases the uptake of mineral micronutrients to plants via controlled release ( Kabiri et al., 2017 ; Li et al., 2019 ; Carneiro et al., 2022 ; Mohammadi Alagoz et al., 2022 ). These effects on soil nutritional traits are positive for plant growth and physiology ( Lahiani et al., 2015 ; Juarez-Maldonado et al., 2019 ) and GO may also benefit by protecting against other plant-harming factors ( Arikan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the effects of CNMs on crop growth is gradually being focused on in the era of food crisis. Some research have shown that CNMs can inhibit the apparent growth of crops while being cytotoxic and genotoxic. , However, there is also a group of studies demonstrating that CNMs promote the germination and growth of crop seeds and even enhance the ability of plants to resist harsh environments (e.g., drought). , It can be speculated that the results of different effects of CNMs on plants greatly depend on the plant species, type of CNMs, particle size and concentration, and growth environment. At present, we still lack a systematic assessment about the interactions between CNMs and crops.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on GO as an antimicrobial agent have shown that low concentrations of GO can extend the vase life of cut flowers ( He et al., 2018 ). GO can directly increase the activities of antioxidant enzymes and the contents of some plant hormones ( Zhao et al., 2022 ) and can also effectively improve the water retention capacity of plants ( Zhao et al., 2020 ). However, there are few research results in the area of the preservation of fresh-cut flowers by using nanomaterials, and there are no studies on the fresh-keeping effect of GO combined with preservatives on fresh-cut flowers.…”
Section: Introductionmentioning
confidence: 99%